Factors Affecting Problems in Accounting Service of theAccounting Offices in Southern Area - กายพันธ์ ปรัศนีย์; โจนส์ สุพินดา; บิลละเต๊ะ อาอีฉ๊ะ (Parichart Journal, 2017)
This research is a study of problems in accounting services of accounting offices in the southern region. The purposes of this study are: 1) To study the knowledge of bookkeepers in accounting offices in the southern region, 2) To study the problems of accounting services of accountants in accounting offices in the southern region, and 3) To study problems in accounting services of Southern Accounting Offices. The populations used in the study were 410 professional accountants in accounting service of the accounting offices in Southern Thailand. The questionnaire was used as a research tool. The researcher collected data by sending a mail questionnaires. The study populations consisted of 148 respondents (36.10% of the population). The data were analyzed by means of mean (xˉ ) and multiple regression analysis. The results showed that accountants had the most knowledge in corporate registration. Knowledge in tax planning and knowledge in accounting system was the second and the third respectively. Moreover, accounting problems of the accountants revealed that the offices had the most difficulty about contact the coordinator with customer. More problems in a continual self - improvement and operational problems of bookkeepers were in secon and third respectively. Furthermore, the study of the factors affecting accounting problems found that the factor was related to the nature of the accounting office about the number of customers. In addition, factors related to the professional knowledge of accountants were knowledge of accounting systems, knowledge of auditing and tax planning at significant level of 0.05